2017
DOI: 10.1111/dom.12938
|View full text |Cite
|
Sign up to set email alerts
|

Insulin degludec: Lower day‐to‐day and within‐day variability in pharmacodynamic response compared with insulin glargine 300 U/mL in type 1 diabetes

Abstract: AimTo compare day‐to‐day and within‐day variability in glucose‐lowering effect between insulin degludec (IDeg) and insulin glargine 300 U/mL (IGlar‐U300) in type 1 diabetes.Materials and methodsIn this double‐blind, crossover study, patients were randomly assigned to 0.4 U/kg of IDeg or IGlar‐U300 once daily for two treatment periods lasting 12 days each. Pharmacodynamic variables were assessed at steady‐state from the glucose infusion rate profiles of three 24‐hour euglycaemic glucose clamps (days 6, 9 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
137
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 14 publications
5
137
1
8
Order By: Relevance
“…They also have larger reductions in rates of hypoglycaemia and likelihood of hypoglycaemia, and a lower risk of treatment discontinuation compared with those initiating treatment with glargine U300. These data are consistent with previous observations from a pharmacokinetic/pharmacodynamic study of degludec and glargine U300 that identified the potential of degludec to result in a lower risk of hypoglycaemia and a relatively higher dose potency compared with glargine U300 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also have larger reductions in rates of hypoglycaemia and likelihood of hypoglycaemia, and a lower risk of treatment discontinuation compared with those initiating treatment with glargine U300. These data are consistent with previous observations from a pharmacokinetic/pharmacodynamic study of degludec and glargine U300 that identified the potential of degludec to result in a lower risk of hypoglycaemia and a relatively higher dose potency compared with glargine U300 …”
Section: Discussionsupporting
confidence: 92%
“…Prior to publication of the DELIVER D+ and BRIGHT studies, it was anticipated that use of degludec would result in lower rates of hypoglycaemia than use of glargine U300, as is the case in comparisons of degludec with insulin glargine U100. This assumption was based on the pharmacodynamic evidence that degludec has a lower day‐to‐day and within‐day variability of glucose‐lowering effect than glargine U300, which may enable tighter glycaemic control with a lower risk of hypoglycaemia . However, in the DELIVER D+ and BRIGHT studies, no differences were found in rate of hypoglycaemia between degludec and glargine U300.…”
Section: Introductionmentioning
confidence: 99%
“…These properties have been demonstrated across different patient populations in several experimental laboratory studies [20, 21]. In the clinical setting, insulin degludec has consistently demonstrated lower rates of overall confirmed, nocturnal confirmed and severe hypoglycaemia compared with other basal insulins [22–24].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin degludec (IDeg) is a basal insulin with a unique mode of protraction that provides an ultra‐long duration of action, exceeding 42 hours, and low day‐to‐day variability in blood glucose‐lowering effect compared with insulin glargine U100 and U300 . Randomized controlled trials (RCTs) in adults, using a treat‐to‐target approach, have demonstrated that IDeg is associated with a reduced risk of hypoglycaemia, vs other insulin analogues, at equivalent levels of glycaemic control …”
Section: Introductionmentioning
confidence: 99%